Achieving high initial coulombic efficiency and plateau capacity in coal-based hard carbon anodes via synergistic doping and soft carbon coating - Jinchao Cui; Ya Wang; Mengxiang Wang; Liming Wang; Yongle Wang; Weihao Shi; Gaohui Du; Wenqi Zhao; Qingmei Su; Lingpeng Yan; Yongzhen Yang (Chemical Engineering Journal, 2026)

Load regulation capability enhancement of a coal-fired power unit integrated with renewable energy and flexible energy storage - Keying Li; Xiwei Ke; Liming Cui; Yang Zhang; Hai Zhang; Junfu Lyu (Fuel, 2026)

Data-driven intelligent modeling for superheater wall temperature prediction and operational optimization of 1000 MW deep peak shaving coal-fired power plants - Xingliang Ji; Yanming Wang; Xiang Ma; Liming Cui; Jiawei Wang; Yongzhong Ni; Hongyuan Li; Tao Wang; Yongsheng Zhang; Hong Xu (Fuel, 2026)

Multi-dimensional metabolic engineering and enzyme engineering in Escherichia coli for highly efficient biosynthesis of 2,5-furandicarboxylic acid - Yanan Cui; Peiyi Zhang; Renjie Miao; Mengqi Zhao; Liqiang Fan; Xu Li; Yongjun Qiu; Chen Deng; Liming Zhao (Bioresource Technology, 2026)

A loofah-based microalgae-bacteria symbiosis drives efficient nutrient removal from low-C/N wastewater: high biomass characterization and mechanism insights - Zhuochao Liu; Meiqi Ren; Han Ji; Hongli Lu; Liming Yang; Dan Cui; Yongzhen Peng (Environmental Research, 2026)

Selective catalytic oxidation of ammonia by efficient FeOx in coal ash: insights from experimental and DFT studies - Yili Zhang; Su Zhang; Binxin Fang; Liming Cui; Yixiang Zhang; Wenzhen Zhang; Houzhang Tan; Ming Li; Xuebin Wang (Fuel, 2026)

Pharmacovigilance signal detection of central nervous system demyelinating diseases following human papillomavirus vaccination: data mining and signal analysis based on the VAERS database - Nan Yang; Xinliang Cui; Leimin Xi; Liming He; Yue Zhou; Haoyu Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Decoding the effect of intermittent feeding strategy on the performances of modular moving bed constructed wetland: Nitrogen removal and antimicrobial resistance dissemination - Lei Zhou; Jiawei Xie; Liming Zhang; Xueqing Sui; Weicong Wang; Jianshi Huang; Shuangqi Wu; Naxin Cui; Shengbing He; Shuiping Cheng (Journal of Hazardous Materials, 2026)

A graph-based C-BOM framework integrating multi-view xBOM data for efficient product carbon footprint assessment - Weitong Liu; Liming Wang; Fangyi Li; Lin Kong; Xingyuan Xiao; Yitong Wang; Yuqi Cui; Boyun Wang; Liuyuan Li (Journal of Cleaner Production, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Multiscale hydrodynamic optimization and energy valorization in hydrogen-based membrane biofilm reactors: unraveling the lumen-shell interaction - Yanxia Xu; Peifeng Deng; Jinyi Tian; Ming Sun; Yuanyuan Qian; Liming Cui; Jinyang Zhang; Xuejing Yang (Journal of Water Process Engineering, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Effect of swirl number and oxygen mole fraction on the ignition characteristics of ammonia-coal co-firing - Dezheng Li; Wenzhen Zhang; Liming Cui; Yang Zhang; Hai Zhang; Junfu Lyu (Fuel, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Differential effects of vegetation types on regional carbon stocks in China: A meta-analysis-based integrated assessment of above-ground and surface soil carbon pools - Guannan Cui; Wenchao Li; Yihao Meng; Liming Dong (Environmental Development, 2026)

Exploring the potential mechanism of Chinese herbal medicine Fuzi on aplastic anemia based on UHPLC-MS/MS method combined with network pharmacology and molecular docking - Wenjian Wei; Yuping Si; Zonghong Li; Xuewei Yin; Guodong Ma; Jingbo Shi; Changnian Li; Liming Yu; Wei Zheng; Yan Wang; Kui Liu; Ruirong Xu; et al. (Natural Product Research, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Impact of concentrated flow and shallow water table on pesticides trapping efficiency of vegetative filter strips – A case study of Northeast China - Liming Yan; Yang Ou; Yuanyuan Sui; Huiping Liu; Yang Deng; Qi Cui; Minglian Shang (Soil and Tillage Research, 2025)

An integrated land use–carbon modeling framework for net carbon emissions and spatial optimization in Northeast China - Jianhang Cui; Zezhu Wei; Xinlin Li; Chengcheng Yuan; Liming Liu; Dingxiang Zhang (Journal of Cleaner Production, 2025)

A quantitative study on the influencing pathways of aerosol acidity: the non-neglectable role of non-ideality - Hanze Cui; Yaxing Du; Hui Zhang; Mingqi Deng; Qi Zhang; Weihua Chen; Shuzhen Su; Xihua Li; Sayantan Sarkar; Liming Yang; Xuemei Wang; Shiguo Jia (Atmospheric Environment, 2025)

Deformation Rate Effects in the Circumferential Strain-Controlled Post-Peak Loading Tests - Guanghao Cui; Fanzhen Meng; Wei Wang; Pengyuan Liu; Yuantao Wen; Zhufeng Yue; Hui Zhou; Liming Zhang (Rock Mechanics and Rock Engineering, 2025)

Macrophage membrane-based biomimetic nanocarrier system for enhanced immune activation and combination therapy in liver cancer - Wei Ni; Mingzhu Zhang; Yueni Mo; Wei Du; Hui Liu; Zhaosong Wang; Yanfen Cui; He Zhang; Zhiyong Wang; Liming Liu; Hui Guo; Ruifang Niu; et al. (Drug Delivery and Translational Research, 2025)

Assessment of the major factors influencing the efficiency of vegetated filter strips under concentrated flow conditions — a case study in Northeast China - Yang Ou; Yang Deng; Liming Yan; Qi Cui; Baixing Yan; Minglian Shang; Huiping Liu; Jibin Wang (Journal of Soils and Sediments, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

Semantic segmentation-based observation pose estimation method for tomato harvesting robots - Lizhong Dong; Licheng Zhu; Bo Zhao; Ruixue Wang; Jipeng Ni; Suchun Liu; Kaikang Chen; Xuezhi Cui; Liming Zhou (Computers and Electronics in Agriculture, 2025)

How does landscape vegetation configuration regulate local channel initiation in a rapidly expanding micro-tidal system? - Dawei Wang; Junhong Bai; Chuanhui Gu; Olivier Gourgue; Jean-Philippe Belliard; Liyue Cui; Yinghai Ke; Liming Xue; Lixiang Wen; Stijn Temmerman (Journal of Hydrology, 2025)

Sensitive shrubland and unique urbanization patterns: the key to understanding emerging towns growth in arid regions - Qi Zhang; Junling He; Chunying Ren; Cun Chang; Wenxi Tang; Xifeng Ju; Adilai Saitiniyaz; Xin Guo; Liyang Cui; Liming Liu (Environmental Monitoring and Assessment, 2025)

Pesticides trapping performance of vegetative filter strips in black soil region, Northeast China: controlled experiments and VFSMOD-W modeling - Liming Yan; Xinhong Wang; Yang Ou; Shujiang Pang; Qi Cui; Xia Hou (Ecological Engineering, 2024)

Photothermal enhanced antibacterial chitosan-based polydopamine composite hydrogel for hemostasis and burn wound repairing - Liming Chang; Yanai Chen; Min Zhou; Yuanwei Gao; Yong Wang; Wenjuan Li; Zhe Cui; Chengyan Zhou; Yingna He; Jianglei Qin (Carbohydrate Polymers, 2024)

Synergistic optimization of baffles and aeration to improve the Light/Dark cycle of microalgae photobioreactor for enhanced nitrogen removal performance: Computational fluid dynamics and experimental verification - Yuanqi Liu; Zhuochao Liu; Zhensheng Xiong; Yanni Geng; Dan Cui; Spyros G. Pavlostathis; Houxing Chen; Qingchun Luo; Genping Qiu; Qiaohong Dong; Liming Yang; Penghui Shao; et al. (Bioresource Technology, 2024)

The impact of hollow core-shell nanozymes in biosensing: A case study of p-Fe3O4@PDA@ZIF-67 - Xiangyu Ma; Yaoying Cui; Kexing Zhu; Xiufang Zhu; Lijing Zhang; Liming Guo; Liangdong Feng; Jiadong Zhang; Yihong Wang; Ling Xia (Analytica Chimica Acta, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Effect of dietary Bifidobacterium animalis subsp. lactis BLa80 on growth, immune response, antioxidant capacity, and intestinal microbiota of juvenile Japanese seabass (Lateolabrax japonicus) - Peng Xu; Kuopeng Cui; Liming Chen; Shaoshu Chen; Zheng Wang (Aquaculture International, 2024)

Metal element-based adsorbents for phosphorus capture: Chaperone effect, performance and mechanism - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Chemosphere, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Rationally designed calcium carbonate multifunctional trap for contaminants adsorption - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Science of The Total Environment, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Lanostane triterpenoids from mycelia-associated Ganoderma sinense and their anti-inflammatory activity - Liming Teng; Chan Wang; Baokai Cui; Jingsong Zhang; Shuai Zhou; Xinhua Pan; Feng Pan; Yucheng Dai; Na Feng (Phytochemistry, 2023)

In situ coupling of MnS-MoS2 bimetallic sulfide on nickel foam by [MnMo9O32]6− platform for advanced hydrogen evolution - Boxin Xiao; Shifa Ullah Khan; Guannan Cui; Liming Dong; Chunjing Zhang; Qiong Wu; Haijun Pang (Clean Technologies and Environmental Policy, 2023)

An EGCG-mediated self-assembled micellar complex acts as a bioactive drug carrier - Chao Liu; Hao Wu; Hongxia Duan; Yan Hou; Shuangqing Wang; Yanhong Liu; Xintong Zhang; Heming Zhao; Liming Gong; Hongshuang Wan; Bowen Zeng; Xiuquan Quan; et al. (Food Chemistry, 2023)

Buffered loofah supported Microalgae-Bacteria symbiotic (MBS) system for enhanced nitrogen removal from rare earth element tailings (REEs) wastewater: Performance and functional gene analysis - Yuanqi Liu; Zhuochao Liu; Dan Cui; Liming Yang; Haiyu Wang; Spyros G. Pavlostathis; Yanni Geng; Zhensheng Xiong; Penghui Shao; Xubiao Luo; Shenglian Luo (Chemosphere, 2023)

A pilot scale study on the treatment of rare earth tailings (REEs) wastewater with low C/N ratio using microalgae photobioreactor - Haiyu Wang; Zhuochao Liu; Dan Cui; Yuanqi Liu; Liming Yang; Houxing Chen; Genping Qiu; Yanni Geng; Zhensheng Xiong; Penghui Shao; Xubiao Luo (Journal of Environmental Management, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Experimental assessment of Soil/metal interface adhesion behaviours of EPB shield Machines - Jian Cui; Gongyun Xu; Yong Fang; Zhongtian Chen; Zhigang Yao; Liming Tao; Liming Qu (Tunnelling and Underground Space Technology, 2023)

Enhanced ammonia nitrogen removal from actual rare earth element tailings (REEs) wastewater by microalgae-bacteria symbiosis system (MBS): Ratio optimization of microalgae to bacteria and mechanism analysis - Zhuochao Liu; Dan Cui; Yuanqi Liu; Haiyu Wang; Liming Yang; Houxing Chen; Genping Qiu; Zhensheng Xiong; Penghui Shao; Xubiao Luo (Bioresource Technology, 2023)

Directed synthesis of a new decamolybdate-encapsulated nanocage framework by mixed-ligands for light-driven hydrogen generation - Chunjing Zhang; Shuang Ma; Guannan Cui; Liming Dong; Fengyang Sui; Xiao Liu; Haijun Pang (Clean Technologies and Environmental Policy, 2022)

Impact of the Three Gorges Dam on the Quality of Riverine Dissolved Organic Matter - Fanchao Xu; Liming Chen; Yifan Xu; Han Gao; He Cui; Peiyun Wei; Xiaolei Qu (Bulletin of Environmental Contamination and Toxicology, 2020)

Relationship Between the Spatiotemporal Distribution of Dominant Small Pelagic Fishes and Environmental Factors in Mauritanian Waters - Narcisse Ebango Ngando; Liming Song; Hongxing Cui; Shuangquan Xu (Journal of Ocean University of China, 2020)

Mechanical Model on Water Inrush Assessment Related to Deep Mining Above Multiple Aquifers - Liming Yin; Kai Ma; Juntao Chen; Yanchao Xue; Ziqi Wang; Boqiang Cui (Mine Water and the Environment, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Vimentin Promotes Astrocyte Activation After Chronic Constriction Injury - Pengfei Xue; Liming Chen; Xiongsong Lu; Jinlong Zhang; Guofeng Bao; Guanhua Xu; Yuyu Sun; Xiaofeng Guo; Jiawei Jiang; Haiyan Gu; Zhiming Cui (Journal of Molecular Neuroscience, 2017)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

GmSGT1 is differently required for soybean Rps genes-mediated and basal resistance to Phytophthora sojae - Qiang Yan; Xiaoxia Cui; Liming Su; Na Xu; Na Guo; Han Xing; Daolong Dou (Plant Cell Reports, 2014)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Streptacidiphilus jiangxiensis sp. nov., a novel actinomycete isolated from acidic rhizosphere soil in China - Ying Huang; Quingfeng Cui; Liming Wang; Carlos Rodriguez; Erika Quintana; Michael Goodfellow; Zhiheng Liu (Antonie van Leeuwenhoek, 2004)